Payment and Delivery System Innovations: Patient‐reported Outcomes from the Comprehensive Care for Joint Replacement Evaluation. (20th August 2020) - Joneydi, R.; Trombley, M.; Roe, D.; Buatti, L.; Schneider, K.; Morrall, I.; McNeely, J.
Abstract : Research Objective: The Comprehensive Care for Joint Replacement (CJR) model is intended to encourage participant hospitals to reduce Medicare payments by coordinating care with the physicians, postacute care (PAC) providers, and other providers involved in an episode of care for a lower extremity joint replacement (LEJR), which comprises the surgery plus the services provided in the 90 days after hospital discharge. Although participant hospitals are incentivized to improve or maintain quality of care, reductions in institutional PAC attributable to the model could have adverse effects on patient recovery and care experiences.1 We surveyed Medicare fee‐for‐service (FFS) beneficiaries a few months after LEJR surgery to document their self‐reported functional status, pain, satisfaction with care management and overall recovery, care transitions, and dependence on caregivers for help with activities of daily living (ADLs). These patient‐reported outcomes are important indicators of quality that cannot be measured using secondary data. Study Design: From 171 metropolitan statistical areas (MSAs) that met CJR eligibility criteria, the Centers for Medicare & Medicaid Services (CMS) randomly selected 67 for CJR and 104 for the control group. Participation in CJR was mandatory for all hospitals in the 67 selected MSAs during the time covered by our analysis. We surveyed a stratified random sample of Medicare FFS beneficiaries who had LEJR surgery in CJR hospitals and a matched group of beneficiaries who had surgery in control hospitals. Patients received the survey approximately 90 to 120 days after hospital discharge. We estimated risk‐adjusted differences between CJR and control respondents on all outcomes. Population Studied: Medicare FFS beneficiaries who had LEJR surgery in March, April, August, or September 2017 were sampled from the CJR intervention group (7, 604 beneficiaries) and the control group (7, 188 beneficiaries). We oversampled patients with hip fractures to assess results for beneficiaries who may be most sensitive to care changes made by hospitals in response to CJR model incentives. Response rates for the survey were similar for the CJR and control groups (70.7% and 71.4%, respectively). Principal Findings: The CJR model did not have a significant impact on patient‐reported functional status, pain, satisfaction with care management and overall recovery, and care transitions. The only significant difference was that CJR respondents reported needing more caregiver help putting on or taking off clothes after returning home than did control respondents. On a 100‐point scale, the difference was ‐2.3 points ( P < .01). All measures were similar for CJR and control respondents with hip fractures. Conclusions: The CJR model resulted in a small increase in reported caregiver help needed after patients returned home. Functional status and satisfaction with care and recovery roughly 90 to 120 days after hospital discharge, however, were not affected by the model, indicating that concerns about dependence on caregivers did not translate to worse functional recovery or satisfaction with care. Implications for Policy or Practice: Other evaluation results show that CJR reduced Medicare payments by reducing institutional PAC.1 Despite lower use in institutional PAC, the model did not affect patient‐reported outcomes and satisfaction. [1] https://innovation.cms.gov/Files/reports/cjr-secondannrpt.pdf Primary Funding Source: Centers for Medicare and Medicaid Services.